Peripheral Neuropathy in Rheumatoid Arthritis Patients: An Electroneurophysiological Study - Lale Akbulut Aktekin; Hilmi Gözlükaya; Hatice Bodur; Pınar Borman; Özlem Köz (Archives of Rheumatology, 2009)
Objective: The aim of this study was to evaluate the frequency of peripheral nervous system involvement with electrophysiological studies in rheumatoid arthritis (RA) patients whose neurological examination findings were within the normal range. Material and Methods: Fifty-six RA patients and 32 healthy control subjects were included. Demographic characteristics, duration of disease and drug use of the patients were recorded. Laboratory variables and Ritchie articular index were used to evaluate disease activity. Electrophysiological studies were performed in all patients and control subjects. Median, ulnar and peroneal nerve motor nerve conduction studies (CVs), F wave, and median, ulnar, and sural nerve sensory CVs were recorded. Results: The frequency of neuropathy was higher in the patients with RA than in the control group. Neuropathy was detected in 20 (36%) RA patients: 3 (5%) had sensorimotor polyneuropathy, 7 (13%) had low sural sensory nerve conduction or absence of action potentials, 2 (4%) had carpal tunnel syndrome, 6 (11%) had low amplitude peroneal compound muscle action potentials, 1 (2%) had low amplitude peroneal compound muscle action potential and low ulnar sensory nerve conduction, and 1 (2%) had low sural and ulnar sensory nerve conduction. Neuropathy was determined in 5 of 13 patients using corticosteroids and in 15 of 43 patients who were not using corticosteroids. There was no statistically significant difference between the electrophysiologic findings of subgroups in terms of the corticosteroid therapy and positivity of Schirmer test and rheumatoid factor. There was no correlation between the electrophysiological parameters and disease activity in patients with RA. In the control group, 2 (6%) cases had electrophysiologically determined neuropathy; frequency of neuropathy was higher in the patients with RA when compared with the control group, and the difference was statistically significant (p<0.01). Conclusion: Clinical evaluation of neuropathy in RA patients is difficult since neuropathic symptoms are frequently confused with arthritis. To detect neuropathy earlier in patients with RA, electrophysiological studies are recommended as routine diagnostic procedure even in the absence of clinical nerve involvement. (Turk J Rheumatol 2009; 24: 62-6)